Evaluasi Implementasi Sistem Informasi Pemerintahan Daerah (SIPD) dalam Penatausahaan Keuangan Daerah di Sektetariat Daerah Kabupaten Wonogiri Tahun 2022-2025 - Rhobi Dwi Pamungkas; Supartini; Syahriar Abdullah (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
This study aims to describe the implementation of the Regional Government Information System (SIPD) in Regional Financial Administration at the Regional Secretariat of Wonogiri Regency, along with the constraints encountered and the efforts made to overcome them. This research uses a qualitative approach with data collection techniques in the form of interviews, observation, and documentation. The results show that the implementation of the SIPD in Financial Administration at the Wonogiri Regional Secretariat is in accordance with the Wonogiri Regent Regulation Number 11 of 2021 concerning the System and Procedures for Regional Financial Management of Wonogiri Regency. The implementation of SIPD at the Regional Secretariat, specifically concerning regional financial accounting and reporting, meets the criteria for the suitability of cash expenditure procedures, the suitability of bookkeeping and reporting governance, and the consistency of user accountability. The main constraints in the implementation of the SIPD financial administration at the Wonogiri Regional Secretariat are: (a) difficulty accessing the server at certain times due to simultaneous use by all regional governments, (b) application imperfections leading to repeated system changes and refinements, (c) differences in operating procedures or input cycles, (d) the need for caution in technical data input, and (e) limited access to the required financial reports. The efforts undertaken to overcome these constraints include: (a) the Regional Government establishing rotating schedules for data input to distribute the workload, (b) updating the classification, codification, and nomenclature of planning and regional finance, while coordinating with the SETDA regarding technical issues, (c) exercising caution when inputting expenditure and revenue transactions, (d) preparing manuals related to the necessary financial reports, and (e) officially applying for additional viewer access rights through the local SIPD administrator. These efforts have proceeded well and significantly aid the SIPD execution at the Wonogiri Regional Secretariat.